DIAGNOSTIC MATHEMATICAL MODEL OF A HYDRAULIC DAMPER OF HELICOPTER ROTOR SLEEVE - U. A. Borisov; B. A. Solov’Ev (Научный вестник МГТУ ГА, 2016)
The article presents an example of the implementation of mathematical modeling in practice of overhaul of units of the helicopter hydraulic system. In particular, it sets out the methodology for constructing diagnostic mathematical model of a hydraulic damper rotor head. A procedure for the analysis of the hydraulic characteristics of the damper valve to determine the flow channel valve defects is suggested.